Diagnosis and Treatment of Multiseptate Gallbladder with Recurrent Abdominal Pain - Turgut Karaca; Omer Yoldas; Bulent Caglar Bilgin; Selma Bilgin; Ender Evcik; Saadet Ozen (Case Reports in Medicine)
Laparoscopic cholecystectomy is usually performed for gallstones or polyp of the gallbladder. Multiseptate gallbladder is a rare congenital malformation. Although several asymptomatic cases have been described, patient usually present with right upper abdominal pain. We present a 29-year-old female patient with multiseptate gallbladder, cholecystectomy was performed, and her abdominal pain and gastrointestinal complaints have resolved.